Studies on reflex action in judo - Ikai, M. (Association for the Scientific Studies on Judo, Kodokan, 1958)
The posture and movement of the human body are under the control of the will, but behind it lies an important factor, reflex regulation. The reflex which regulates posture is called postural reflex. Postural reflex has mostly been studied in decerebrate animals, and is said to take place in the central nervous system below the cerebrum. For some time it was thought than in man this postural reflex was manifested only under pathological condition of the cerebrum, but recently it has been made clear that under certain conditions it does occur even in healthy individuals. In every day life this postural reflex is obscured by voluntary regulation, and to observe it in an isolated form is rather difflcult. However, when an external force is suddenly and unexpectedly applied to the body, or when one suddenly adopts a certain posture or carriage this postural reflex may be clearly elicited. Fukuda and Nishihata have reported on their observations on postural reflex during the performance of sports, and Nishihata has commented on the importance of postural reflex in judo. The present study was made in order to investigate the rationality of the various techniques o f judo from the point of view of postural reflex of both the offensive and the defensive during a throwing performance.